2014
DOI: 10.1245/s10434-014-3493-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing for Preoperative Risk Assessment before Pancreaticoduodenectomy for Cancer

Abstract: 2014) 'Cardiopulmonary exercise testing for preoperative risk assessment before pancreaticoduodenectomy for cancer.', Annals of surgical oncology., 21 (6). pp. 1929-1936. Further information on publisher's website:http://dx.doi.org/10.1245/s10434-014-3493-0Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1245/s10434-014-3493-0.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 20 publications
2
46
1
Order By: Relevance
“…AT represents the upper limit of workload beyond which prolonged exercise is impossible (28). It has been shown to be an objective marker of CVR (19)(20)(21)(22)28). Patients undergoing EVAR have a high-prevalence of AKI risk-factors and are at significant risk of AKI (1,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT represents the upper limit of workload beyond which prolonged exercise is impossible (28). It has been shown to be an objective marker of CVR (19)(20)(21)(22)28). Patients undergoing EVAR have a high-prevalence of AKI risk-factors and are at significant risk of AKI (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular reserve (CVR) is a parameter that is modifiable through various interventions before non-urgent surgery. Estimation of CVR is increasingly being used to identify those at highest risk of complications after surgery (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiopulmonary exercise testing that measures oxygen consumption and carbon dioxide elimination may identify a subgroup of patients with increased operative risk but mortality is low, so the use of the test as a discriminatory factor is not fully adequate [45].…”
Section: Operability Assessmentmentioning
confidence: 99%
“…19,39 In practical terms, this degree of variability is potentially significant when considering outcomes in perioperative assessments. 5,11,13,15,22,[39][40][41] In two recent reviews, Levett et al 5,12 summarized studies assessing the association between preoperative VT and postoperative outcomes. These studies among different surgery candidates (including major intra-abdominal, colon, rectal, hepatobiliary, hepatic resection, liver transplant, upper gastrointestinal, bariatric, cystectomy, and AAA repair procedures) showed that values below 9-12 mLO 2 Ákg -1…”
Section: Discussionmentioning
confidence: 99%